Terapi Swedish Massage menurunkan tingkat kecemasan Lansia di Balai Pelayanan Sosial Tresna Wredha (BPSTW) Unit Budi Luhur Yogyakarta - Anastasia Suci Sukmawati; Ega Pebriani; Arif Adi Setiawan (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2018)
Abstract: Older will experiencing physical, psychological, and psychosocial changes will cauthat will lead to the new problem. Anxiety is one of the problems among older people. Complementary therapy is used to reduce a persons anxiety, namely yoga, meditation, aromatherapy, and relaxation through massage. This study was conducted to determine the effect of Swedish massage on the level of elderly anxiety. Methodology: The design of this study was a quasy experiment with one group pretest-post test design. Respondents in this study were elderly who experienced anxiety by using a total sampling technique in which as many as 15 elderly at the Nursing home of Social Service Center (BPSTW) Budi Luhur Bantul Unit Yogyakarta. The Standard operational procedure of Swedish massage therapy used as a guidance of intervention, while HARS instruments was used to measure the level of anxiety among older people. Respondents measured their level of anxiety before and after a Swedish massage for 1 week. The results of the study were analyzed by Wilcoxon test. Results: There were 8 people (53.3%) in the medium level of anxiety before the Swedish massage given). The anxiety level of older people after intervention was mild level of anxiety as many as 8 people (53.3%). Changes in anxiety levels before and after Swedish massage intervention showed a difference of 2.00. Wilcoxon test results were obtained with a p-value of 0.008 <0.05. Conclusion: Swedish massage therapy able to reduce the level of anxiety among older people at BPSTW Budi Luhur Yogyakarta. Keywords: Swedish massage, anxiety Abstrak: Berbagai macam perubahan akan dialami oleh lansia seperti perubahan fisik, psikologi, maupun psikososial akan menimbulkan masalah baru pada lansia salah satunya adalah kecemasan. Tehnik alternatif yang dapat digunakan untuk menurunkan kecemasan seseorang yaitu seperti yoga, meditasi, aromaterapi, dan relaksasi melalui pijat (massage). Penelitian ini dilakukan untuk mengetahui pengaruh Swedish mas- sage terhadap tingkat kecemasan lansia. Metodologi: Desain penelitian ini adalah quasy experiment dengan one group pretest-post test design. Responden pada penelitian ini adalah lansia yang mengalami kecemasan dengan menggunakan teknik total sampling yaitu sebanyak 15 lansia di Balai Pelayanan Sosial tresna Wredha (BPSTW) Unit Budi Luhur Bantul Yogyakarta. Instrumen penelitian adalah instrument HARS. Responden diukur tingkat kecemasannya sebelum dan setelah dilakukan Swedish massage selama 1 minggu. Hasil penelitian dianalisis dengan uji Wilcoxon. Hasil : Tingkat kecemasan pada lansia di BPSTW Budi Luhur Bantul Yogyakarta sebelum diberikan Swedish massage kategori sedang sebanyak 8 orang (53,3%). Tingkat kecemasan sesudah diberikan Swedish massage kategori ringan sebanyak 8 orang (53,3%). Perubahan tingkat kecemasan sebelum dan sesudah diberikan Swedish massage menunjukkan perbedaan sebesar 2,00. Hasil uji Wilcoxon diperoleh dengan nilai p-value 0,008 < 0,05. Diskusi : Swedish massage berpengaruh terhadap tingkat kecemasan pada lansia di BPSTW Budi Luhur Bantul Yogyakarta. Kata kunci: Swedish massage, kecemasan, lansia